Acquired Angioedema of the Glottis, Larynx and Neck in a Patient Affected by SLE: Case Report. Issue 1 (16th May 2018) - Scollo, S.; La Camera, G.; Neri, S.; Grasso, C.; Cubisino, R.; Bonsignore, C.; La Rosa, V.; Astuto, M.
Acquired angioedema is a rare complication of systemic lupus erythematosus (SLE). It is generally secondary to C1 inhibitor deficiency due to antibody formation directed against the C1 inhibitor molecule. Face, mouth, tongue, lips, extremities and genitalia are generally involved but also respiratory and gastrointestinal mucosa may be affected. We report a case of a young woman with SLE who presented a severe airway obstruction caused by angioedema. We discuss her diagnostic and therapeutic management including a review of the literature.